Congenital tuberculosis in preterm infants in a high-burden setting in southwest China: a single-center cross-sectional study - Zhuang, Xiaoling; Xu, Wanting; Xu, Wen; Shi, Yan; Xiao, Mei; Rihei, Awai; Dong, Wenbin; Bian, Chengpeng (Frontiers in Pediatrics, 2025)
BackgroundCongenital tuberculosis (CTB) is an extremely rare and potentially life-threatening infection in premature infants that is frequently misdiagnosed. There is still a lack of thorough characterization of this condition in preterm neonates, particularly in high TB-burden settings.MethodsPremature infants with CTB were identified from hospital medical records from January 2016 to December 2023 in a high-burden, resource-limited neonatal intensive care unit (NICU) in southwest China. Diagnosis was based on etiology and clinical evidence. Data extracted included demographics, maternal history of tuberculosis (TB) exposure, symptoms, laboratory markers, microbiological findings, imaging findings, treatment regimens, and prognosis. These were evaluated during the pre-diagnosis, diagnosis, and posttreatment stages.ResultsA total of 11 premature infants with CTB were included. Maternal TB was common in this cohort; 7 of the 11 mothers were diagnosed with TB following in vitro fertilization and embryo transfer. Clinical manifestations were atypical and consisted primarily of non-specific symptoms, including low fever, shortness of breath, poor reaction, less eating, and coughing. Laboratory findings during the active phase of CTB revealed statistically significant elevations in C-reactive protein levels (P = 0.001), thrombocytopenia (P = 0.007), hyponatremia (P = 0.040), hypocalcemia (P = 0.022), and hypomagnesemia (P = 0.025). Sputum acid-fast bacillus (AFB) smear was positive in 4 out of 11, while gastric juice AFB smear was positive in 6 out of 11. Mycobacterial liquid culture produced the highest positivity with 7 out of 11, followed by solid culture and interferon-gamma release assays with 5 out of 11. All nucleic acid amplification tests were positive, and chest CT scans showed abnormalities in each patient. Among the patients, five experienced liver function impairment after anti-TB treatment, as evidenced by elevated alanine aminotransferase levels.ConclusionsIn this study, preterm infants with CTB frequently demonstrated non-specific clinical signs with a reversible pattern of inflammation, anemia, thrombocytopenia, and electrolyte disturbances that normalized after anti-TB therapy. These patterns, together with maternal TB risk or in vitro fertilization and embryo transfer history, may raise clinical suspicion and justify the early use of nucleic acid amplification testing, and generalizability outside this setting requires larger, controlled cohorts.